PERANCANAGAN APLIKASI ACCOUNT PAYABLE SUBSIDIARY DENGAN PEDEKATAN MODEL PHASED DEVELOPMENT - Edy Nasri; Widyawati Widyawati; Sodikin Sodikin (Program Studi Sistem Informasi, Universitas Banten Jaya, 2022)
In this era of technological development, a lot of stored information requires applications that can support all activities, effectively and efficiently, but not many companies have implemented the application as a whole. one of which is Amaris Hotel Cilegon which has not used applications for recording purchases, receipts and controlling debts. Debt data processing still uses spreadsheets which are prone to various problems. Therefore, this study aims to analyze work activities by looking at the system that is running at Amaris hotel Cilegon. The data on this study was collected using literature study methods and field studies to get accurate data results. Application creation uses native PHP language programming, with MySQL database and Class Bootstrap as a framework interface, while in the design of application system development the method used is the RAD method with Phased Development Model. In this study, the author designed and developed the Account Payable Subsidiary application that can provide the company's debt control features at any time, record-keeping relationships with payable accounts and performed only one process in the recording process receiving, to produce output in the form of values listed in receiving journals and payable account journals and can be directly used as the basis for making financial statements by Bookkeeper Accounting Supervisor.